2019
DOI: 10.1111/bcp.13942
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety and tolerability of the novel β‐hCG derived immunomodulatory compound, EA‐230

Abstract: Aims EA‐230 is a newly developed synthetic linear tetrapeptide (AQGV) derived from the chorionic gonadotropin hormone (β‐hCG). We investigated the pharmacokinetics, safety and tolerability of EA‐230 in healthy subjects using different administration strategies. Methods Double‐blind, randomized, placebo‐controlled, dose‐escalating phase I studies in healthy subjects using intravenous administration were conducted. In the single dosage study, 32 subjects were assigned to four single dosage groups (1, 3, 10 or 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Furthermore, all AEs in the active groups were of mild intensity and regarded unlikely or unrelated to study drug treatment. These results are consistent with earlier human phase I trials focusing on safety of EA‐230 in the absence of systemic inflammation reported elsewhere in this issue and indicate that EA‐230 seems to be safe in dosages up to 90 mg/kg/h. Further safety data with higher dosages and/or longer administration duration would be needed to study a possible exposure‐dependent effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, all AEs in the active groups were of mild intensity and regarded unlikely or unrelated to study drug treatment. These results are consistent with earlier human phase I trials focusing on safety of EA‐230 in the absence of systemic inflammation reported elsewhere in this issue and indicate that EA‐230 seems to be safe in dosages up to 90 mg/kg/h. Further safety data with higher dosages and/or longer administration duration would be needed to study a possible exposure‐dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the pharmacokinetic profile of EA‐230 reveal a large volume of distribution, a very rapid systemic clearance and accordingly a short half‐life. A finding of interest is the substantially higher plasma concentrations of EA‐230 compared to the phase I continuous dosing study reported elsewhere in this issue, which was performed and analysed within the same institute, using exactly the same dosing regimens (15, 45 and 90 mg/kg/h for 2‐hours). The elimination rates (β) were, however, comparable to those found in the phase I continuous dosage study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations